A retrospective study of 237 dogs hospitalized with suspected acute hemorrhagic diarrhea syndrome: Disease severity, treatment, and outcome. (27th February 2021) - Dupont, Nana; Jessen, Lisbeth Rem; Moberg, Frida; Zyskind, Nathali; Lorentzen, Camilla; Bjørnvad, Charlotte Reinhard
Abstract: Background: Few studies have investigated management and outcome in dogs with acute hemorrhagic diarrhea syndrome (AHDS), and there is a paucity of data on dogs with concurrent signs of sepsis. Objectives: To report outcome in dogs with suspected AHDS according to disease severity and antimicrobial treatment, and to evaluate effect of fluid resuscitation on clinical criteria. Animals: Two hundred thirty‐seven dogs hospitalized with suspected AHDS. Methods: Retrospective study based on medical records. Disease severity was evaluated using AHDS index, systemic inflammatory response syndrome (SIRS) criteria, and serum C‐reactive protein (CRP) according to 3 treatment groups: No, 1, or 2 antimicrobials. Results: Sixty‐two percent received no antimicrobials, 31% received 1 antimicrobial, predominantly aminopenicillins, and 7% received 2 antimicrobials. At admission, median AHDS index was 13 (interquartile range, 11‐15), which decreased significantly after the first day's hospitalization ( P  < .001) for all groups. Compared with no antimicrobials (7%), more dogs had ≥2 SIRS criteria in the antimicrobial groups (15% and 36%, respectively). C‐reactive protein (CRP) correlated positively with AHDS index at hospitalization ( P  < .001). Across treatment groups, rehydration markedly reduced number of clinical SIRS criteria. Survival to discharge was 96%, lower for dogs receiving 2 antimicrobials (77%, P  < .05). Conclusions and Clinical Importance: The majority of dogs hospitalized with suspected AHDS improve rapidly with symptomatic treatment only, despite signs of systemic disease on initial presentation. The often‐used SIRS criteria might be a poor proxy for identifying dogs with AHDS in need of antimicrobial treatment, in particular when hypovolemic. The role of CRP in clinical decision‐making or prognostication warrants further investigation.